Komunikasi Efektif Dalam Bingkai Kepemimpinan Organisasi - Yanuar Ada Zega (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
Effective communication within the framework of organizational leadership is something that seems important to be studied properly. Organization is one dimension in which there are leaders and subordinates (followers). Today it is not uncommon for leaders to fail as motivators for their followers. This failure can be seen from the lack of cooperation between leaders and subordinates. This event greatly affects the level of success of the organization itself. Responding to this, the author offers an idea as an alternative problem solving, namely that leaders can actually be good motivators for their followers. One of the most powerful figures in making it happen is through effective communication. This effort aims to find a solution to the communication crisis that occurs among today's organizational leaders. This paper uses a qualitative method with a library research approach. The result of this paper is that if every leader builds good communication, then his leadership will run smoothly and be successful.